Visibility impacts at Class I areas near the Bakken oil and gas development. (4th May 2018) - Gebhart, Kristi A.; Day, Derek E.; Prenni, Anthony J.; Schichtel, Bret A.; Hand, J.L.; Evanoski-Cole, Ashley R.
ABSTRACT: Oil and gas activities have occurred in the Bakken region of North Dakota and nearby states and provinces since the 1950s but began increasing rapidly around 2008 due to new extraction methods. Three receptor-based techniques were used to examine the potential impacts of oil and gas extraction activities on airborne particulate concentrations in Class I areas in and around the Bakken. This work was based on long-term measurements from the Interagency Monitoring of Protected Visual Environments (IMPROVE) monitoring network. Spatial and temporal patterns in measured concentrations were examined before and after 2008 to better characterize the influence of these activities. A multisite back-trajectory analysis and a receptor-based source apportionment model were used to estimate impacts. Findings suggest that recent Bakken oil and gas activities have led to an increase in regional fine (PM2.5 —particles with aerodynamic diameters <2.5 µm) soil and elemental carbon (EC) concentrations, as well as coarse mass (CM = PM10 –PM2.5 ). Influences on sulfate and nitrate concentrations were harder to discern due to the concurrent decline in regional emissions of precursors to these species from coal-fired electric generating stations. Impacts were largest at sites in North Dakota and Montana that are closest to the most recent drilling activity. Implications : The increase in oil and gas activities in the Bakken region of North Dakota and surrounding areas has had a discernible impact on airborne particulate concentrations that impact visibility at protected sites in the region. However, the impact has been at least partially offset by a concurrent reduction in emissions from coal-fired electric generating stations. Continuing the recent reductions in flaring would likely be beneficial for the regional visual air quality.